Role of visual abilities in mathematics learning: An analysis of conceptual representation - Rif'at, Mohamad; Sudiansyah, Sudiansyah; Imama, Khoirunnisa (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: In mathematics education, the understanding of concepts is often influenced by students' visual abilities, making conceptual representation crucial in facilitating comprehension of the material.Aim: This study aims to analyze the role of visual abilities in facilitating the understanding of mathematical concepts through conceptual representation.Method: This research combines quantitative analysis with the use of attribute control diagrams to evaluate data obtained from tasks designed to test students' visual abilities in a mathematical context. These tasks include the manipulation of visual representations and problem-solving using geometric concepts.Results: The findings indicate that 80% of the sample possessed visual abilities that did not meet the expected index, showing a wide variation in students' visual representation abilities. Additionally, most students (70%) were more likely to choose familiar geometric representations in problem-solving, despite difficulties in manipulating more complex concepts.Conclusion: This study demonstrates that students often struggle to effectively utilize visual representations, preferring algebraic approaches that do not fully exploit the potential of conceptual representation. The findings suggest that an increased focus on developing visual abilities, especially in conceptual representation, could strengthen mathematical understanding. Further research is needed to develop intervention strategies that can help students overcome gaps in their visual abilities.